A pilot randomized trial on the usability and acceptability of an app (MyIBDDiet) to improve the self-management of anti-inflammatory diet for individuals with inflammatory bowel disease: A protocol paper - Ravneet Kaur; Kendall van Diepen; Somayeh Raiesdana; Kaitlyn Delaney Chappell; Lekan Ajibulu; Michal Gozdzik; Brendan Halloran; Frank Hoentjen; Karen I. Kroeker; Farhad Peerani; Carla M. Prado; Dina Kao; et al. (PLoS ONE, 2026)
The role of diet in the management of inflammatory bowel disease (IBD) is increasingly recognized with recent guidelines providing specific dietary recommendations. Although mobile health apps targeting diet and lifestyle habits in IBD are emerging, few are designed for self-management or have been formally evaluated for effectiveness. We have co-designed a diet guidance and tracking app (MyIBDDiet) with and for patients with IBD with the aim of improving overall diet profile. We will be conducting a 60-day single-centre pilot randomized trial of 40 IBD patients randomized in 1:1 ratio to MyIBDDiet app or usual care. Participants in the usual care group will crossover to the MyIBDDiet app group after 30 days. Primary outcome is usability assessed using a mixed method quantitative [Theoretical Framework of Acceptability (TFA), mHealth App Usability Questionnaire (MAUQ)], and qualitative approach (semi-structured interviews). Secondary outcomes include clinical efficacy evaluated by change in diet quality [Mini-EAT questionnaire, Automated Self-administered 24-Hour Dietary Assessment Tool (ASA-24), Healthy Eating Index (HEI), Mediterranean Diet Serving Score (MDSS)], changes in biomarkers of processed food intake (spot urine sodium and chloride), changes in IBD disease activity [Patient Reported Outcome (PRO2 and PRO3), C-reactive protein, fecal calprotectin], changes in quality of life [EuroQol-5 Dimension (EQ-5D), Short Inflammatory Bowel Disease Questionnaire (SIBDQ)] and safety. Exploratory outcomes include changes in fecal microbiome and serum and fecal metabolome. Additional quantitative data will be collected from the digital analytics of MyIBDDiet app. The pilot data generated will inform the design of an adequately powered randomized trial and future mobile app development and evaluation by providing a framework for evaluation of clinical effectiveness. Trial registration ClinicalTrials.gov Identifier: NCT06683105 . Registered on 8 November 2024.